Playing Sherlock Holmes : Interviews with John Wood, Robert Stephens and Christopher Lee. - Pointer, Michael (Andrews UK, 2017)
Playing Sherlock Holmes contains three verbatim interviews - with John Wood, Robert Stephens and Christopher Lee - about their very different experiences of appearing as Holmes on stage and screen. The interviews were conducted in 1974. At the time, John Wood was appearing on stage in an acclaimed revival of William Gillette's play Sherlock Holmes, a Royal Shakespeare Company production; Robert Stephens had recently completed The Private Life of Sherlock Holmes for film director Billy Wilder; and Christopher Lee - who had a role as Mycroft Holmes in that film - had earlier played the lead role.